USE OF SEWAGE SLUDGE IN THE AGRICULTURE: WORKABILITY STUDY - ROSA, DANIEL B.; PAULA JR, DURVAL R. DE (Revista Brasileira de Engenharia de Biossistemas, 2009)
There are a growing number of industries which are adjusting their environmental laws and gettingtheir 14000 ISO certificates, nowadays. These adjustments cross the treatment of industrial anddomestic effluents according to their activities, thus generating the sludge of wastewater treatmentplants (WWTP). Usually the sludges are addressed to industrial landfills without evaluating the potentialfor reuse of waste into other activities, somehow burdening the costs of effluent treatment, losing anexcellent opportunity to increase waste generator revenue ́s. However, the sludge reuse requires adetailed study of sludge ́s characteristics and its eventual adaptation for the intended destination,and, in many cases, the pollutant potential of the material can prevent any type of reuse. Aiming toreduce costs with sludge disposal in landfills, it was developed such a workability study, through thecharacterization of WWTP sludge not industrial unit of a major automaker in order to demonstratepossible alternatives to the fitness of the WWTP sludge, aiming to get mud with enough quantity andquality to enable the stabilization and treatment for its use as biossolid in agricultural activities developedby this company.